2013
DOI: 10.1155/2013/975350
|View full text |Cite
|
Sign up to set email alerts
|

Trichosanthes kirilowiiEthanol Extract and Cucurbitacin D Inhibit Cell Growth and Induce Apoptosis through Inhibition of STAT3 Activity in Breast Cancer Cells

Abstract: Trichosanthes kirilowii tuber is a traditional medicine which exhibits various medicinal effects including antidiabetic and anticancer activities in several cancer cells. Recently, it was reported that Cucurbitacin D (CuD) isolated from Trichosanthes kirilowii also induces apoptosis in several cancer cells. Constitutive signal transducer and activator of transcription 3 (STAT3), which is an oncogenic transcription factor, is often observed in many human malignant tumor, including breast cancer. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…In vivo studies confirmed the inhibitory effect of cucurbitacin B on the expression of HIF-1 α proteins, leading to a decrease growth of HeLa cells in a xenograft tumor model [77]. Cucurbitacin D isolated from the plant has also been shown to suppress proliferation of HT-29 human colon cancer cells [78] and the compound could be potent therapeutic agent for breast cancer by blocking tumor cell proliferation and inducing apoptosis through suppression of STAT3 activity [79] and it could also induce apoptosis in human hepatocellular carcinoma cells [80]. …”
Section: Discussionmentioning
confidence: 97%
“…In vivo studies confirmed the inhibitory effect of cucurbitacin B on the expression of HIF-1 α proteins, leading to a decrease growth of HeLa cells in a xenograft tumor model [77]. Cucurbitacin D isolated from the plant has also been shown to suppress proliferation of HT-29 human colon cancer cells [78] and the compound could be potent therapeutic agent for breast cancer by blocking tumor cell proliferation and inducing apoptosis through suppression of STAT3 activity [79] and it could also induce apoptosis in human hepatocellular carcinoma cells [80]. …”
Section: Discussionmentioning
confidence: 97%
“…Consequently, activated STAT3 has been found in numerous solid tumors, including breast, prostate, pancreas, and ovarian cancers. Recent studies have shown that STAT3 is constitutively activated in approximately 70% of breast cancers [4] but is most associated with triple-negative breast cancer (TNBC), which lacks estrogen receptors, progesterone receptors, and HER2 expression [5]. In breast cancer cells, active STAT3 was found in TNBC cells alone.…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbitadienol can form a variety of cucurbitanetype triterpenoid glycosides which occur mainly in the family Cucurbitaceae. These include mogrosides, as in Siraitia grosvenorii, and cucurbitacins in Trichosanthes kirilowii [16], Cucumis sativus [17], and Cucurbita pepo [18]. It has been known as the basic backbone of cucurbitane-type triterpenes.…”
Section: Introductionmentioning
confidence: 99%